Milk Street bakes - Kimball, Christopher; Hirsch, J. M.; Locke, Michelle; Smolin, Ari; Yanagihara, Dawn; Card, Matthew (Voracious, 2024)
The American baking repertoire may be unparalleled in our claim to pies, biscuits, and cakes. But step off a plane in London, Mexico City, Istanbul, or Paris, and you realize how much more there we can learn about the art of simple, delicious baked goods. We found a simple Spanish almond cake that uses no wheat flour. Loaf cakes that balance the sugar with slightly-bitter rye. Super-creamy Basque cheesecake that requires no water bath. Mexican sweet corn cake made in a blender. Or Catalan biscotti, sticky chocolate cake from Sweden, and crispy spinach and cheese borek from Türkiye. We also include forgotten American recipes such as maple-glazed hermits and new classics such as peanut butter banana cream pie. And we go beyond sweets to include yeasted breads, savory tarts, pizzas, and flatbreads (some made in a skillet in minutes). Most of these recipes are easier than you'd think, from beer pretzels to Danish dream cake. But in baking, the little things count--so Milk Street is here to help you avoid pitfalls with recipes that you can count on. Our promise to you is that you will become the best baker you know! --